Measuring the burden of herpes zoster disease in Costa Rica - Emmanouil Rampakakis (Acta Médica Costarricense, 2017)
Background : Herpes zoster is a distressing illness that significantly reduces patients’ quality of life. However, Costa Rican data regarding the clinical burden of herpes zoster and associated health care resource utilization is limited. This study aimed to assess the zoster-associated burden evaluating pain, impact on quality of life and health care resource utilization in a Costa Rican sample.Methods: Herpes zoster patients recruited in Costa Rica at a private geriatric practice were enrolled at various time points during a zoster episode and were actively followed over 6 months. Outcomes including zoster-associated pain, quality of life and health care resource utilization were assessed via patient self-reported questionnaires.Results : 50 zoster patients were included 68.0% female, mean (SD) age = 69.5 (10.8) years. Zoster-associated pain decreased over time while quality of life improved though without full base recovery. The highest health care resource utilization included doctor’s office (98.0%), emergency room (60.0%) and specialists (60.0%) visits. Sixteen (32.0%) patients were hospitalized mean (SD)= 4.3 (4.1) days.Conclusion : Similar to other Latin American countries, high herpes zoster burden was observed in a private geriatric practice in Costa Rica, supporting the need for early intervention and preventive strategies, one of such could be the implementation of a HZ vaccination program.